Estimating the actual and potential adoption rates and determinants of NERICA rice varieties in Nigeria - Dontsop Nguezet, Paul M.; Diagne, A.; Okoruwa, V.; Ojehomon, V.; Manyong, Victor M. (Informa UK Limited, 2013)
The paper uses the average treatment effect (ATE) to estimate the population potential adoption rates of the New Rice for Africa (NERICA) varieties in Nigeria when awareness and access to their seed are not constrained to farmers. It thus extends previous works in the literature that have focused on estimating potential adoption rates when only awareness of technology is not a constraint to farmers. The adoption gaps because of lack of awareness and access to seed, and the determinants of adoption are estimated as well. Results show that the potential NERICA adoption rate in Nigeria will be 54% if the entire population is aware and up to 62% if they have access to NERICA seed. The actually observed 19% adoption rate implies a population adoption gap of 35% and 43% because of lack of awareness and access to NERICA seed, respectively. It is also inferred from these results that, when awareness is not a constraint, about 8% of the population will fail to adopt NERICA because of lack of access to its seed. Also farmers with secondary education and farmers with access to extension services are more likely to adopt NERICA than farmers without them.